Kualitas Fisik Dan Nilai Sensori Super Bumbu Tabur Berbasis Ikan Bandeng (Chanos chanos) Dan Rumput Laut (Kappaphycus alvarezii) - Gevbry Ranti Ramadhani Simamora; Ni'matus Sholihah; Mirza Gulam Ahmad; Gressty Sari Br Sitepus; Siti Munfarida (Universitas Negeri Gorontalo, 2026)
Seasoning is a condiment product that is widely used to improve the taste of food, but generally has low nutritional value. The development of seasonings based on food ingredients with high nutritional value is necessary so it is necessary to produce products that not only provide taste, but also better nutritional benefits. Milkfish (Chanos chanos) is a good source of protein and minerals, while Kappaphycus alvarezii seaweed is rich in dietary fiber and bioactive compounds which have the potential to be used as raw materials for super seasonings. This research aimed to determine the effect of differences in the concentration of milkfish flour and seaweed flour on the physical and sensory quality of super sprinkles and determine the best formula that can be accepted by consumers. This research used an experimental method with four comparison treatments of seaweed flour and milkfish flour, namely F1 (0%: 100%), F2 (20%: 80%), F3 (30%: 70%), and F4 (40%: 60%). The selected super seasoning formula was determined based on hedonic tests and the level of panelist acceptance on the attributes of appearance, color, aroma, taste, texture and colorimetric analysis. The results showed that the difference in concentration of seaweed flour and milkfish flour influenced the level of panelists' acceptance of super seasoning. Formula F2 (20% seaweed: 80% milkfish) is the best formula with the highest taste preference score of 6.88 and obtained the highest average score for all sensory attributes tested. Based on these results, the F2 formula has the potential to be developed as a super product for seasonings that is rich in nutrition and has a good level of consumer acceptance.